Effectiveness of COVID-19 vaccines and mortality risk in Peru: A population-based study of matched cohorts - López, Lucy (2022)
Introduction. The Peruvian COVID-19 vaccination plan started on March 2021 and consists of three types of vaccines. After 8 months it has reached 55.18% of the target population with two dosis of vaccines and 3.5 million people have not yet received the 2nd dose. There is the need to estimate the mortality with the current vaccination plan because there is limited information of its effectiveness. Objective. To estimate the current effectiveness of the COVID-19 vaccination plan to prevent mortality in population above age 18. Methods. Matched cohorts case control study of hospitalized patients diagnosed of COVID-19 from February 9, 2020 through October 27, 2021. 107 410 subjects from the State´s Peruvian Open Data National Platform were included from which 2254 dead hospitalized subjects selected had two vaccine doses and 2254 had not. Effectiveness was estimated by modelling survival method of Kaplan Mayer and the Cox (HR). Results. The estimated effectiveness of the vaccination plan was 80.4% (IC 95% 78.2% – 82.5%). The COVID-19 lethality rate in vaccinated was 17.5% vs 78.8% in non-vaccinated. The median survival time in the hospitalized vaccinated cohort was 42 days (IC 95%: 31-64), vs 7 days (IC 95%: 6-7) in non-vaccinated (p < 0.001). Conclusions. The vaccines utilized in the Peruvian program are highly effective to prevent mortality in hospitalized for COVID-19. Results might improve should coverage and completeness of two doses increase.